The millipede family Ammodesmidae (Diplopoda, Polydesmida) in western Africa - VandenSpiegel, Didier (Pensoft Publishers, 2012)
Abstract. Ammodesmidae are represented in western Africa by two species of a single genus, Ammodesmus Cook, 1896 (= Cenchrodesmus Cook, 1896, syn. n.). The type-species Ammodesmus granum Cook, 1896 (= Cenchrodesmus volutus Cook, 1896, syn. n.) is redescribed, based on neotype selection, as well as on additional samples, often containing numerous specimens, from Liberia, Guinea and the Ivory Coast. A new species is described from Mount Nimba, Guinea: Ammodesmus nimba sp. n.